Improving Bottom Service Learning Outcomes Through The Ball Throwing Approach To Students Of State Middle School 37 Makassar - Aldi Aldi; hikmad hakim; Arifuddin Usman; Muh. Adnan Hudain; Ians Aprilo (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
The purpose of the study was to determine the improvement of learning outcomes of lower serves of bolavoli games through the approach of playing throwing balls to students of SMP Negeri 37 Makassar. This research is a class action research using several cycles (pre-cycle, cycle I and cycle II) and begins with a pre-cycle, to see an increase in student learning outcomes after being given a ball throwing game. The results showed that in the pre-cycle activities, the number of students who completed learning was 1 student or all students were not complete as many as 21 students or 5% of students were complete and 95% of students were not complete with an average learning outcome of 44.45. Cycle I the number of students who completed learning was 4 students and 18 students were not complete or as many as 18% of students were complete and 82% of students were not complete with an average learning outcome of 64.27, while in cycle II there was a significant increase in student learning completeness to 22 complete students or 100% with an average learning outcome of 87.18. The conclusion of the ball throwing game can improve the learning outcomes of the lower service of bolavoli in students of SMP Negeri 37 Makassar with an average increase in learning outcomes of 42.73.